비골 피판을 이용한 하악 및 하악과두 재건의 장기간 임상적 평가 - 안강민(Kang-Min Ahn); 정헌종(Hun-Jong Chung); 염학렬(Hak-Ryol Ryom); 김항진(Hang-Jin Kim); 김윤태(Yoon-Tae Kim); 황순정(Soon-Jung Hwang); 명훈(Hoon-Myoung); 김명진(Myung-Jin Kim); 김성민(Soung-Min Kim); 장정원(Jeongwon Jahng); 이종호(Jong-Ho Lee) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2005)
Purpose of study: The temporomandibular joint (TMJ) occupies a key functional role in mastication and contributes to normal deglutition, speech as well as cosmesis. When a large amount of mandible including the condyle head is resected, it is very difficult to reconstruct it as a functional unit. In this retrospective study, we present the functional, radiographic and cosmetic results of reconstructed temporomandibular joint using free fibular flap. Patients and Methods: Total 12 patients (M:F = 6:6) who underwent condylar reconstruction with the fibular flap were interviewed and examined by radiographs and Bio-PAK. Mean follow up periods was 47.7±20.0 months and the average age was 38.7±15.3 years. Remodeling of condyle and function of TMJ were evaluated and facial contour was judged subjectively. Results: All flaps were viable and no immediate postoperative complication had happened. One patient showed decreased mouth opening, so interpositional gap arthroplasty was performed. The resorption rates of reconstructed fibular were minimal and the condyle heads were changed into domeshaped neocondyle after 2 years. All patients had normal diet and no speech difficulty was reported. Nine patients were satisfied with their facial contour but three patients complained about the depression of cheek. Conclusion: The reconstruction of TMJ with free fibular flap was reliable methods and very effective means of restoring mandibular function. The functional and morphologic results were excellent and showed little complications. KCI Citation Count: 1